A Novel Wireless Sensor Networks Structure Based on the SDN - Zhi-jie Han; Wanli Ren (International Journal of Distributed Sensor Networks)
Since the SDN (Software Defined Network) technology based on OpenFlow was born, domestic and foreign research institutions have had increasing attention to this emerging field. The OpenFlow technology which is known for standardization and compatibility network virtualization has brought a lot of innovative solutions in the field of research. As the wireless sensor network node is complex and difficult to move and the network topology is changing rapidly with time, this requires a routing protocol for it to be able to adapt to this high topology change. Because traditional WSNS protocol communication needs to consider energy consumption, load balancing and other factors, it is difficult to find one to take into account all aspects of network algorithms. In this paper, we put forward a new solution for WSNS in accordance with the OpenFlow technology research in the application of traditional network.